A COMPARISON OF YOUTUBE SHORTS FEATURES WITH REGULAR YOUTUBE VIDEOS IN ARABIC VOCABULARY LEARNING - Haidar, Ghani Ahmad; Tatang, Tatang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2025)
This study aims to compare the effectiveness of the Youtube Shorts feature with regular Youtube videos in teaching Arabic vocabulary. The research design employed is a literature review, where data were collected from various scholarly articles, research reports, and other relevant sources related to the utilization of both Youtube features in the learning context. Data analysis was conducted descriptively to evaluate the advantages and disadvantages of each feature based on aspects such as display design, time flexibility, and material accessibility. The results show that Youtube Shorts excels in capturing attention through interactive short videos but has limitations in delivering complex materials. Conversely, regular Youtube videos provide flexibility for more in-depth content delivery but require longer viewing times. This study recommends the synergistic use of both features, tailored to learning objectives and audience preferences, to enhance the effectiveness of Arabic vocabulary learning. Future studies are expected to conduct direct experiments with specific subjects to empirically evaluate learning outcomes.